The PENGARUH NILAI PRODUK DOMESTIK REGIONAL BRUTO DAN PERSENTASE PENGANGGURAN TERHADAP TINGKAT INFLASI PROVINSI SUMATRA SELATAN (2018-2023): Pengaruh Nilai Produk Domestik Regional Bruto Dan Persentase Pengangguran Terhadap Tingkat Inflasi Provinsi Sumatra Selatan (2018-2023) - Erlangga, Brayen Albacino; Mulyani, Ninik; Pagarani, Ratu Yanridho; Awalia, Mufliatun Ni’matul (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2025)
This research focuses on the issue of how Gross Regional Domestic Product (GRDP) and Unemployment Rates affect the inflation rate in the South Sumatra Province during the period of 2018-2023. GRDP is the total value of all goods and services produced in a region within a specific period, while unemployment is a significant factor considered in assessing the inflation rate in a region. In this research, the researcher uses a case study of the South Sumatra Province, which is one of the largest provinces with a considerable population and diverse commodities. This is a quantitative study that utilizes secondary data obtained from the Central Bureau of Statistics of the South Sumatra Province. The discussion in this research falls under the study of Macroeconomic Theory, where GRDP of the South Sumatra region is designated as Variable X1, Unemployment as Variable X2, and the Inflation Rate as Variable Y. The analysis in this research is conducted using statistical data analysis with SPSS Version 23. The results of the SPSS analysis indicate that GRDP and Unemployment have an influence of 46.7% on the inflation rate. According to existing theories, GRDP and Unemployment can be significant factors in inflation.